Evaluation of the impact of E-procurement on buyers and suppliers in a value chain - Ramamurthy Murali Mohan (2008)
The report evaluates the impact of the e-Procurement in Apple Computer’s value chain. The focus is on the forecasting and transactions for direct procurement and to provide a common platform between Apple and the suppliers irrespective of the internal systems used by small, medium or large suppliers.